Hubungan konsumsi protein harian dan status gizi dengan kejadian karies gigi molar pertama bawah permanen pada siswa sekolah dasar - Sutrio, Sutrio; Rahmadi, Antun; Purnomowati, RR. Ratnasari Dyah; Sumardilah, Dewi Sri; Mulyani, Roza (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Dental caries is a common oral health problem in school-aged children, particularly in the lower permanent first molars, which are susceptible to decay. Daily protein intake is thought to play a crucial role in dental health because protein contributes to the formation of hard dental tissue and saliva acts as a natural defense against caries. Purpose: To analyze the relationship between daily protein consumption and nutritional status and the incidence of caries in the lower permanent first molars in elementary school students. Method: A cross-sectional study design was used, involving 150 fourth- and fifth-grade students selected using total sampling. Nutritional status was determined based on Body Mass Index for Age (BMI/A). Caries examinations were performed clinically by dental health professionals. Data were analyzed bivariately using the Chi-Square test. Results: 67.6% of children with insufficient daily protein intake experienced caries, compared with 36.8% in the adequate intake group (p = 0.001; OR = 3.57). Meanwhile, 62.5% of children with abnormal nutritional status experienced caries compared to 50% of children with normal nutrition, but this relationship was not statistically significant (p = 0.24; OR = 1.67). Conclusion: There is a significant association between daily protein consumption and the incidence of caries in the lower first permanent molars. Keywords: Dental Caries; Nutritional Status; Permanent Molars; Protein Intake; School Children. Pendahuluan: Karies gigi merupakan masalah kesehatan mulut yang umum pada anak usia sekolah, khususnya pada gigi molar pertama bawah permanen yang rentan mengalami kerusakan. Asupan protein harian diduga berperan penting dalam kesehatan gigi karena protein berkontribusi pada pembentukan jaringan keras gigi dan fungsi saliva sebagai pertahanan alami terhadap karies. Tujuan: Untuk menganalisis hubungan antara konsumsi protein harian dan status gizi dengan kejadian karies gigi molar pertama bawah permanen pada siswa sekolah dasar. Metode: Desain penelitian cross-sectional dengan sampel 150 siswa kelas 4 dan 5 yang dipilih secara total sampling. Status gizi ditentukan berdasarkan Indeks Massa Tubuh per umur (IMT/U). Pemeriksaan karies dilakukan secara klinis oleh tenaga kesehatan gigi. Data dianalisis secara bivariat menggunakan uji Chi-Square. Hasil: Sebanyak 67.6% anak dengan asupan protein harian kurang mengalami karies, dibandingkan dengan 36.8% pada kelompok asupan cukup (p = 0.001; OR = 3.57). Sementara itu, 62.5% anak dengan status gizi tidak normal mengalami karies dibandingkan 50% anak dengan gizi normal, namun hubungan ini tidak signifikan secara statistik (p = 0.24; OR = 1.67). Simpulan: Ada hubungan yang signifikan antara konsumsi protein harian dengan kejadian karies gigi molar pertama bawah permanen. Kata Kunci: Anak Sekolah; Asupan Protein; Gigi Molar Permanen; Karies gigi; Status gizi.